Argos Informatiedagen 1999. - Vral, Virginie; Argos, Brussel (Brussel : Argos, 1999)
Van den Abeele, Michael ; Ackerman, Chantal ; Albers, Beatrijs ; Alvim, Fernando ; Atelier Jeunes Cinéastes ; Atrux-Tallau, Laurette ; Aubier, Stéphane ; Ausloos, Anne ; Baes, Pascal ; Barrea, Olivier ; Bats, Isabelle ; Bedel, Delphine ; de Beeck, Hans Op ; Van Beirendonck, Walter ; De Bemels, Anthonin ; Bianchet, Frédérico ; De Bisschop, Sarah ; Blumenthal, Bud ; Boon, Elke ; Borght, Joris Van der ; Bosmans, Laurence ; Braeckman, Dirk ; Brehmer, Andreas ; Brosens, Peter ; Bulckens, Erik ; Bultheel, Jan ; De Busschère, Alec ; Byamba, Sakhya ; Case, Charley ; Cash, Robert ; Catrysse, Wim ; Cioni, Giovanni ; Claerbout, David ; Claessens, Roger ; De Cock, Jan ; Compernol, Luc ; Crabeels, Cel ; Curlet, François ; Van Cutsem, Philippe ; D'Haeseleer, Kurt ; D'Hondt, F.J. ; D'Hondt, Lieve ; Dagonnier, Ronald ; Dans, Michael ; De filmfabriek ; De Humane Groene Boontjes ; Dedobbeleer, Koenraad ; Dekyndt, Edith ; Delafontaine, Jean ; Delmotte, Monsieur ; Delville, Chris ; Dementieva, Alexandra ; Deridder, Jean-Paul ; Devens, Zjuul ; Devos, Danny ; Dirix, Jean-Luc ; Downsbrough, Peter ; Dryvers, Sandrine ; Duclaux, Lise ; Engels, Trudo ; Evrard, David ; Experimental Intermedia ; Factor 44 ; Faes-Dupont, Yves ; François, Michel ; Fron't ; Gaillard, Frédéric ; Garcia, Dora ; Gerard, Pierre ; Geronnez, Alain ; Gillis, Herman ; Gobyn, Luk ; Gregoor, Eddy ; De Gruyter, Jos ; Guns, Patrick ; Hall, Mark ; Halloy, Reynald ; Hänzel & Gretzel ; Harrisson ; Van Hasselt, Mil ; Hechtle, Markus ; Van Hees, Pieter ; Heiremans, Ronny ; Hendrickx, Arnaud ; Hendrix, Dirk ; Heynen, Gunter ; Hortext ; Huberlant, Renaud ; Huybrechts, Jo ; De Jaeger, Peter ; Junius, Justine ; Van Kerckhoven, Anne-Mie ; Kosmopoulos, Kosmas ; Krüger, Peter ; Kuyl, Joris ; Lafontaine, Marie-Jo ; etc.
Informatiedagen van 1999, Beursschouwburg, Brussel, 21 - 24/11/1999
Nederlands & Engels
boek